Case series: effects of an induced molting protocol using levothyroxine in five captive banded penguins (genus Spheniscus) - Park, Ji-Hyung; Seo, Seung-Hyun; Kim, Sang Wha; Kang, Yeong-Hun (Frontiers in Veterinary Science, 2025)
Penguin molts occur annually after breeding, allowing effective waterproofing and temperature regulation. However, aberrant molts frequently occur in penguins, which can lead to health problems if prolonged. Although the exact mechanisms underlying molting in birds remain unclear, some studies have focused on the roles of thyroid and sex hormones in penguins. Previous studies on forced molting using hormonal treatments have shown both success and failure. In particular, the use of synthetic thyroxine (levothyroxine) has mostly not been successful. This study aimed to induce molting by administering commercial levothyroxine to one Humboldt penguin (Spheniscus humboldti) and four African penguins (Spheniscus demersus) with abnormal molting, housed in aquaria. The planned levothyroxine dosing protocol was to start with 25 μg/kg PO q24h for 7 d, then increase it gradually to 50 μg/kg PO q24h for the next 7 d and 75 μg/kg PO q24h for 7 d, followed by a gradual decrease to 50 μg/kg PO q24h for 7 d, and 25 μg/kg PO q24h for the final 7 d. Three penguins received treatment according to this scheduled protocol, two of which initiated molting during the dosing period, while the third began to molt approximately 3 months post-treatment. Another penguin was administered the maximum dose for an additional week, which led to molting in the final week of treatment. In the remaining penguin, the medication was deemed to be insufficiently absorbed because of inadequate drug delivery methods. Consequently, the drug delivery strategy was changed during the 5th week of treatment, and the treatment was extended for an additional 3 weeks beyond the original plan, after which the penguin began to molt. Therefore, all five penguins in this study exhibited molting following oral levothyroxine treatment, suggesting that this is a potential option for inducing molting in banded penguins (Spheniscus sp.) experiencing aberrant molt.